Peningkatan Keterampilan Pembudidaya Ikan Melalui Pelatihan Pembuatan Pakan Herbal Untuk Kelompok Pembudidaya Ikan di Kelurahan Pahandut Seberang, Palangkaraya - Maryani Maryani; Ida Ratnasari; Nursiah Nursiah (Jurnal Pengabdian Pada Masyarakat, 2019)
IMPROVING THE SKILL OF FISH CULTIVATORS THROUGH HERBAL FEED MAKING TRAINING FOR FISH CULTIVATION GROUPS IN PAHANDUT SEBERANG VILLAGE, PALANGKARAYA. The fish farming business carried out by farmers is still traditional in nature, and until now it still relies on factory feed (pellets) as the main feed, besides that frequent disease outbreaks also follow it in fish cultivated in a cage due to frequent tides in the Kahayan River adding significant losses of farmers. Onion-Dayak as a typical Central Kalimantan medicinal plant contains phytochemical compounds, namely alkaloids, glycosides, flavonoids, phenolics, steroids, and tannins, which can be used as herbs. Therefore the author decided to carry out the Community Partnership Program in the form of training on making Dayak onion herbal feed to increase the knowledge and skills of fish farmers about the technique of making Onion-Dayak herbal feed for fish farming. The method used in achieving these objectives is through counseling and training activities. The results achieved after the training were that participants were able to understand and master the material about making Dayak onion herbal feed independently by utilizing raw materials around partner locations, so that fish feed needs during cultivation activities were fulfilled and did not depend on factory-made feed, and aquaculture protected from attacks diseases which ultimately can increase fish production.